Using Spatial Autocorrelation for identification of demographic patterns of Functional Urban Areas in Poland - Kurek Sławomir; Wójtowicz Mirosław; Gałka Jadwiga (Bulletin of Geography. Socio-Economic Series, 2021)
Functional Urban Areas (FUAs) leads to a better knowledge of urban spatial organisation, which may play a significant role in regional policy making and may be helpful in understanding the connection between urbanisation and demographic development. An explanation of population change in urban regions can be associated the second demographic transition comprising fertility decline below replacement level and postponement of births.